Biomimicry of direct veneers with compound resin and indirect restaurations with zirconium silicate - Vílchez-Salazar, Ernesto (2015)
Now we have various materials to for direct restorations in the previous sector. In this case the direct resin was used Beautiful II, which is a nanohybrid compound with optical characteristics of natural teeth. Likewise for indirect restorations exists materials which reproduce the optical characteristics similar to the dental tissues, in this case indirect laboratory resin Ceramage was used, which is a zirconium silicate that combine the advantages of ceramic and resin. In the present clinic case it’s detailed the protocol of the application of the resin Beautiful II and Ceramage. Results: the result high patient expectations because it was possible to restore the teeth involved restoring function loss and especially aesthetics in a suitable manner biomimicking both materials. Conclusions: deep knowledge of both materials to be used as well as the protocols and techniques to follow, led to biomimic the aesthetic results of the previous zone getting translucency, opacity and opalescence very similar in all restored teeth.